Re-membering a Queer Body - Holmes, Morgan (UnderCurrents: Journal of Critical Environmental Studies, 1994)
In the spring 1993 issue of The Sciences, Brown University geneticist Anne Fausto-Sterling, citing the work of John Money, indicates that approximately four percent of the population is, to some degree, intersexual: they either possess physical characteristics of both officially recognized sexes or they have chromosomes which indicate a sex which are 'contradicted' by their physical appearance.1 In Toronto, the four percent figure translates into roughly 88,000 people. Yet little has been written about intersexuality, although its concerns often intersect with those of feminist and queer theory. This paper deals with feminist issues in patriarchal medicine and its relation(s) to intersexuality (and intersexuality's inherent ability to challenge arguments for the 'natural' basis of heterosexuality).
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme matérialiste; intersexuation; ontario; personnes intersexes; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2014; sociologie; thématiques; toronto; violences médicales

Les femmes salariées dans l'Église catholique francophone du Québec : une analyse du rôle de l'idéologie et de ses mécanismes dans le maintien des rapports de pouvoir - Bazinet, Colette (Université du Québec à Montréal, 1994)
Keywords: IREF; amériques; discipline; mémoires/thèses; québec; régions géographiques; sciences humaines; sociologie; thématiques; travail

Le pouvoir dans les groupes de femmes de la région de Québec - Couillard, Marie-Andrée (Recherches sociographiques, 1994)
Les idéaux féministes d'égalité formulés au cours des années 1970 et 1980 sont aujourd'hui confrontés à des discours divers qui pénètrent les groupes de femmes. D'une part, la vision des technocrates les incite à accepter des fonctions instrumentales en retour d'un financement considéré essentiel par plusieurs. La majorité des groupes en sont ainsi venus à offrir des services qui se situent dans le prolongement de ceux offerts par le réseau de la santé et des services sociaux. À travers ces ajustements, les groupes de femmes ne se définissent plus seulement comme des lieux de conscientisation et de résistance, mais bien comme des groupes communautaires travaillant, de concert avec d'autres groupes communautaires, à l'amélioration du bien-être collectif. Les discours savants portant sur le féminisme, sur les conditions de sa mise en oeuvre ou sur le rapport entre l'État et le communautaire rejoignent eux aussi les militantes et affectent de façons diverses le portrait qu'elles tracent de leurs pratiques. C'est cet ensemble complexe dans lequel des rapports de force se nouent quotidiennement que nous voulons décrire et analyser ici.
http://id.erudit.org/iderudit/056826ar
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; canada; discipline; groupes de femmes; histoire et politique; militance; patriarcat; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail

Paradoxes of gender - Lorber, Judith (Yale University Press., 1994)
In this innovative book, a well-known feminist and sociologist challenges our most basic assumptions about gender. Judith Lorber argues that gender is wholly a product of socialization, subject to human agency, organization, and interpretation, and that it is a social institution comparable to the economy, the family, and necessity of gender, she envisions a society structured for equality, where no gender, racial, ethnic, or social class group is allowed to monopolize positions of power.
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; fem1000; genre; identités LGBTQIA2+; premier cycle; périodes historiques; queer; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; socialisation; sociologie; thématiques; états-unis

Sexes et pouvoir : la construction sociale des corps et des émotions - Préjean, Marc (Presses de l'Université de Montréal, 1994)
Keywords: 1900-1999; 1990-1999; amériques; care; corps; cours; différence des sexes; discipline; fem1000; militance; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sociologie; thématiques; émotions